Ambient Communications and Computer Systems RACCCS 2017 - Perez, Gregorio Martinez; Tiwari, Shailesh; Trivedi, Munesh C.; Mishra, Krishn K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book includes high-quality, peer-reviewed papers from the International Conference on Recent Advancement in Computer, Communication and Computational Sciences (RACCCS-2017), held at Aryabhatta College of Engineering & Research Center, Ajmer, India on September 2-3, 2017, presenting the latest developments and technical solutions in computational sciences. Data science, data- and knowledge engineering require networking and communication as a backbone and have a wide scope of implementation in engineering sciences. Keeping this ideology in mind, the book offers insights that reflect the advances in these fields from upcoming researchers and leading academicians across the globe. Covering a variety of topics, such as intelligent hardware and software design, advanced communications, intelligent computing technologies, advanced software engineering, the web and informatics, and intelligent image processing, it helps those in the computer industry and academia use the advances of next-generation communication and computational technology to shape real-world applications.
Neural Network based Novel Detection Technique for Analysis of Pollutant levels in Air -- A Dual Coding Technique to Reduce Dynamic Power Dissipation in Deep Submicron (DSM) Technology -- Short Term Solar Power Forecasting using Random Vector Functional Link (RVFL) Network -- A CSA based Architecture of Vedic Multiplier for Complex Multiplication -- Using Parallel and Distributed Reachability in Model Checking -- Trust Evaluation in Social Network Using Trusted Graph -- Exactly Once Semantics with Real-time Data Pipelines -- Analysis of Online Suspicious Behavior Patterns -- A Review of Biometrics Modalities and Data Mining Algorithms -- Real-Time Eye Detection Method For Driver Assistance System -- Gabor-Max-DCT Feature Extraction Techniques for Facial Gesture Recognition.
Keywords: Telecommunication; Computational intelligence; Data mining; Communications Engineering, Networks; Computational Intelligence; Data Mining and Knowledge Discovery